Genomic characteristics of clinical multidrug-resistant Proteus isolates from a tertiary care hospital in southwest China - Li, Ying; Liu, Qian; Qiu, Yichuan; Fang, Chengju; Zhou, Yungang; She, Junping; Chen, Huan; Dai, Xiaoyi; Zhang, Luhua (Frontiers in Microbiology, 2022)
Multidrug-resistant (MDR) Proteus, especially those strains producing extended-spectrum β-lactamases (ESBL) and carbapenemases, represents a major public health concern. In the present work, we characterized 27 MDR Proteus clinical isolates, including 23 Proteus mirabilis, three Proteus terrae, and one Proteus faecis, by whole-genome analysis. Among the 27 isolates analyzed, SXT/R391 ICEs were detected in 14 strains, and the complete sequences of nine ICEs were obtained. These ICEs share a common backbone structure but also have different gene contents in hotspots and variable regions. Among them, ICEPmiChn2826, ICEPmiChn2833, ICEPmiChn3105, and ICEPmiChn3725 contain abundant antibiotic resistance genes, including the ESBL gene blaCTX-M-65. The core gene phylogenetic analysis of ICEs showed their genetic diversity, and revealed the cryptic dissemination of them in Proteus strains from food animals and humans on a China-wide scale. One of the isolates, FZP3105, acquired an NDM-1-producing MDR plasmid, designated pNDM_FZP3105, which is a self-transmissible type 1/2 hybrid IncC plasmid. Analysis of the genetic organization showed that pNDM_FZP3105 has two novel antibiotic resistance islands bearing abundant antibiotic resistance genes, among which blaNDM-1 is located in a 9.0 kb ΔTn125 bracketed by two copies of IS26 in the same direction. In isolates FZP2936 and FZP3115, blaKPC-2 was detected on an IncN plasmid, which is identical to the previously reported pT211 in Zhejiang province of China. Besides, a MDR genomic island PmGRI1, a variant of PmGRI1-YN9 from chicken in China, was identified on their chromosome. In conclusion, this study demonstrates abundant genetic diversity of mobile genetic elements carrying antibiotic resistance genes, especially ESBL and carbapenemase genes, in clinical Proteus isolates, and highlights that the continuous monitoring on their transmission and further evolution is needed.